Will there be a renaissance in rail transport after 2021? - Henryk Zielaskiewicz; Przemyslaw Ciszak (Przegląd Komunikacyjny)
As year 2021 was announced the year of rail transport, by the decision made by the EU Council and Parliament on 23rd December 2020, the authors of this article present the history of railway development in Europe and in Poland. The directions of changes in transport policy in the last years of previous century and the early years of this century were not positive for the development of railway. Thou, there is an opportunity for this branch of transport to experience a renaissance. In the article some trends of current changes are shown. A year to year increase in traffic congestions as well as the awareness to protect the natural environment cause that this branch of transport has good perspectives of development. The use of modern technology in rolling stock and in passenger transport infrastructure contribute to the increase of speed, reliability and comfort of travelling and what is more regaining the clients. To minimize the negative influence of transport on environment it is crucial to develop cargo transport. Keywords: Railway transport; Train; Railway development